Zubarev's method of a nonequilibrium statistical operator and some challenges in the theory of irreversible processes - Morozov, V.G.; Röpke, G. (Condensed Matter Physics, 1998)
We give a brief review of applications of the method of the nonequilibrium statistical operator developed by D.N.Zubarev to some problems of
nonequilibrium statistical mechanics. Ми подаємо короткий огляд застосування методу нерівноважного
статистичного оператора, розвинутого Д.М.Зубарєвим, до деяких
проблем нерівноважної статистичної механіки.